Fucus spp. as a mercury contamination bioindicator in costal areas (Northwestern Portugal) - Cairrão, E.
Mercury has been considered as one of the most important pollutants in coastal and estuarine areas. Efforts have been made to detect, as early as possible, the effects of this and other metals in several species. Macroalgae, particularly Fucus spp., have been widely used as biomonitors of metal pollution. In this study, three Fucus species (F. spiralis, F. vesiculosus and F. ceranoides) were collected from several sampling sites in Portugal. The concentrations of mercury were determined in three structural parts (holdfast, stipe and receptacles). Two different techniques were used to determine mercury concentrations. Almost all mercury concentrations (in sediments and in water) were below national and international standards. Mercury concentration in the specimens (0.012-0.061 mu g g(-1) for receptacles, 0.028-0.221 mu g g(-1) for stipe and 0.029-0.287 mu g g(-1) for holdfast) was always higher that those obtained for the sediment (0.001-0.112 mu g g(-1)). With few exceptions the contrary was found for receptacles. In general, a good agreement between concentrations of mercury in sediment and Fucus was found. The results indicate that Fucus accumulate mercury and may be a suitable species for use in risk assessment for coast and estuarine areas, by providing valuable information regarding the levels of mercury that will be available for the consumers of Fucus spp.